2009
DOI: 10.1158/1541-7786.mcr-08-0292
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of Connective Tissue Growth Factor in Endothelial Cells by the Microtubule-Destabilizing Agent Combretastatin A-4

Abstract: Incubation of microvascular endothelial cells with combretastatin A-4 phosphate (CA-4P), a microtubule-destabilizing compound that preferentially targets tumor vessels, altered cell morphology and induced scattering of Golgi stacks. Concomitantly, CA-4P up-regulated connective tissue growth factor (CTGF/CCN2), a pleiotropic factor with antiangiogenic properties. In contrast to the effects of other microtubule-targeting agents such as colchicine or nocodazole, up-regulation of CTGF was only detectable in sparse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
23
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 43 publications
(62 reference statements)
4
23
0
Order By: Relevance
“…In accordance with our results, microarray data showed that CTGF was down-regulated upon overexpression of constitutively active AKT, whereas active FoxO1 up-regulated CTGF in HUVEC (10). Furthermore, we observed a role for FoxO transcription factors in CTGF expression induced by TGF-␤, alterations of the cytoskeleton, or inhibition of histone deacetylases (7,8). These data suggested a central role for FoxO transcription factors in endothelial CTGF regulation.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…In accordance with our results, microarray data showed that CTGF was down-regulated upon overexpression of constitutively active AKT, whereas active FoxO1 up-regulated CTGF in HUVEC (10). Furthermore, we observed a role for FoxO transcription factors in CTGF expression induced by TGF-␤, alterations of the cytoskeleton, or inhibition of histone deacetylases (7,8). These data suggested a central role for FoxO transcription factors in endothelial CTGF regulation.…”
supporting
confidence: 91%
“…In endothelial cells, inhibition of PI-3K/AKT signaling led to upregulation of CTGF expression (8). Moreover, knockdown of FoxO1 and FoxO3a by siRNA almost completely inhibited the induction of CTGF, providing evidence for a role of FoxOs in CTGF regulation (7). In accordance with our results, microarray data showed that CTGF was down-regulated upon overexpression of constitutively active AKT, whereas active FoxO1 up-regulated CTGF in HUVEC (10).…”
supporting
confidence: 88%
See 2 more Smart Citations
“…The molecular mechanism of the antiangiogenic properties of TR-644 CA-4 analog was linked to the inhibition of vascular endothelial growth factor-induced phosphorylation of VE-cadherin (Porcù et al, 2013). It has also been suggested that CA-4 may exert its antiangiogenic properties by downregulation of connective tissue growth factor, a negative regulator of angiogenesis (Samarin et al, 2009). Preclinical studies combining the combretastatins with other antiangiogenic agents gave conflicting results.…”
Section: Inhibitors Of Neovascularization/angiogenesismentioning
confidence: 99%